Mechanical properties and mechanisms of alkali-activated slag paste reinforced by graphene oxide-SiO2 composite. (10th December 2022) - Yang, Haibin; Hou, Dongshuai; Zheng, Dapeng; Tang, Luping; Tang, Waiching; Cui, Hongzhi
Abstract: Alkali-activated slag (AAS) binders-based composites are considered potential alternatives to conventional cement-based composites. However, the quasi-brittle mechanical behavior of AAS binders-based composites limits their widespread application. In this study, a graphene oxide-SiO2 (GO-SiO2 ) composite was produced to address this issue. The experimental results showed that the flexural strength of an AAS paste increased by 133.2% with 1.5 wt% GO-SiO2 composite, and its corresponding flexural-to-compressive strength ratio increased 95% i.e. from 0.063 to 0.123. To explore the strengthening mechanism, the stability of the GO-SiO2 composite in alkaline solutions and the dispersion effect of GO-SiO2 composite on the mechanical properties of AAS paste were investigated. The experimental results showed that the prepared GO-SiO2 composite had stable C–O–Si chemical bonds connected GO with hydration products, thereby improving the strength of the AAS paste. The molecular dynamics study revealed the mechanism that the high-dispersed GO-SiO2 composite could improve the mechanical properties of the AAS paste dramatically. Highlights: The prepared GO-SiO2 composite exhibited excellent dispersibility in an alkaline solution. The stability of the C–O–Si chemical bond in the GO-SiO2 composite was investigated. Flexural strength of alkali-activated slag paste increased by 133.2% for the GO-SiO2 modification. Mechanisms of AAS paste reinforced by the GO-SiO2 composite were clarified.